2017
DOI: 10.1002/art.39855
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster and the Risk of Stroke in Patients With Autoimmune Diseases

Abstract: Background Herpes zoster (HZ) is an opportunistic infection caused by varicella zoster virus (VZV), and observed with increasing frequency in patients on immunosuppressive therapies. Prior literature has suggested that the risk of stroke may increase shortly after herpes zoster, but little is known about this association for patients with autoimmune (AI) diseases, who are at increased risk both for zoster and stroke. Methods Medicare data (2006–2013) was used to identify patients with autoimmune diseases. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Additionally, a further increase of stroke risk was observed in RA patients with HZ neurological complications (aHR=1.54, P =0.015). Furthermore, our results showed a 2.3‐fold increased risk of stroke within 90 days after HZ occurrence in RA patients compared with those without HZ ( P =0.02), which is consistent with a recent study for HZ‐related stroke in patients with autoimmune diseases in the United States . Increasing evidence showed that VZV vasculopathy and stroke were associated with HZ .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, a further increase of stroke risk was observed in RA patients with HZ neurological complications (aHR=1.54, P =0.015). Furthermore, our results showed a 2.3‐fold increased risk of stroke within 90 days after HZ occurrence in RA patients compared with those without HZ ( P =0.02), which is consistent with a recent study for HZ‐related stroke in patients with autoimmune diseases in the United States . Increasing evidence showed that VZV vasculopathy and stroke were associated with HZ .…”
Section: Discussionsupporting
confidence: 92%
“…The diagnosis of HZ was required to have been made after the RA identification index date. The complication of HZ was in accordance with a diagnosis code (Table ) . The diagnosis of HZ‐related stroke was required to have been made after the HZ identification index date and was defined by patients with a diagnosis code of stroke (ICD‐9‐CM codes 430‐438).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also does not address whether HZ selectively increases the risk of only GCA. The potential for HZ to trigger other diseases has been previously demonstrated, with HZ events being associated with an increased risk of stroke in the general population and among patients with autoimmune disease . While it is important to understand whether the risk of PMR is also increased following HZ events, we anticipated that administrative data sets would also be prone to misclassification of PMR, given that 1 study found a false‐positive rate of >20% for diagnostic codes of PMR .…”
Section: Discussionmentioning
confidence: 99%
“…HZ events were identified by ICD‐9‐CM code 053.xx from either a hospital discharge or physician visit record. HZ was further classified as complicated (i.e., HZ with meningitis, other nervous system, ophthalmic, or other complications; ICD‐9‐CM codes 053.0–053.8) or uncomplicated (code 053.9), similar to an HZ classification used in previous analyses . HZ treatment was identified by a combination of an HZ event and an accompanying outpatient pharmacy claim for acyclovir, famciclovir, valacyclovir, ganciclovir, or foscavir within 7 days before or after the HZ event date.…”
Section: Methodsmentioning
confidence: 99%